Implementasi Metode Weighted Aggregated Sum Product Assesment Untuk Menentukan Mandor Panen Kelapa Sawit - Gellysa Urva; Welly Desriyati (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Palm oil is an agricultural commodity that has an important role in the palm oil industry. To maximize palm oil production, efficient management is needed, including selecting qualified harvest foremen. This research aims to implement the Weighted Aggregated Sum Product Assessment (WASPAS) method in determining the most suitable oil palm harvest foreman. The WASPAS method was used in this research because it is able to integrate a number of relevant criteria to evaluate the quality of a harvest foreman. These criteria include education, age, experience, knowledge, discipline, leadership and loyalty. The implementation of the WASPAS method is able to provide ranking results that are relevant to the specified criteria. So that users have a more complete and objective picture regarding the determination of prospective oil palm harvest foremen. This helps avoid decisions that are too subjective and can make more informed and appropriate decisions. The results of this research show that the WASPAS method can be used effectively to determine the most suitable harvest foreman. The highest score obtained in the ranking of oil palm harvest foreman selection was 0.863. Implementation of the WASPAS method used can determine the harvest foreman who has the best qualifications according to the needs of users in the company. This can increase the productivity and efficiency of palm oil harvests, as well as have a positive impact on the palm oil industry as a whole